Diversifikasi Rasa Baru Apem Yaqowiyyu Jatinom untuk Meningkatkan Kualitas Produk Unggulan di Kabupaten Klaten - Chayati, Ichda; Widodo, Syukri Fathudin Achmad; Setiadi, Bayu Rahmat (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Apem yaqowiyyu is a traditional snack at every breakfast event in Jatinom District, Klaten Regency. Gradually, apem yaqowiyyu began to be sold every day without waiting for the Saparan ceremony. One of the existing and productive producers of Apem Yaqowiyyu is UKM Apem Yaqowiyyu Bunda Santi. A total of 6 people, namely Mrs. Santi and five workers, have been able to produce apem yaqowiyyu to meet the needs of the local community and tourists. In carrying out business, these SMEs have a significant production problem. The problem is that the limited apem owned is not durable and long-lasting, and the number of variants over the years of opening a business is only five flavors. Solutions that can be resolved based on an agreement between the PKM team and partners are solving production problems. The solution to the production problem is the addition of 5 new flavors that the general public likes. The resulting PKM results are six new flavor variants based on research innovation and science and technology application to partners, including Mocca A, Mocca B, Pisang Kepok, Pisang Raja, Baked Plantain, and Raisins. Based on the PKM team and partner assessment results, Mocca A is in great demand and has the potential to have a high selling value because the quality of the apem filling is premium class.